2007
DOI: 10.1016/j.eurpsy.2007.01.099
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of depressive pseudodementia in the elderly

Abstract: BackgroundThe term depressive pseudodementia has proved to be a popular clinical concept. Little is known about the long-term outcome of this syndrome.AimsTo compare depressed elderly patients with reversible cognitive impairment and cognitively intact depressed elderly patients.MethodsAll patients suffering from moderate or severe depression admitted to St Margaret's Hospital, UK as inpatients or day hospital outpatients between January 1, 1997 and December 31, 1999 (n=182) were screened for entry into the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Although late-life depression may cause some cognitive impairment (i.e. “pseudodementia”), up to 70% of patients with pseudodementia will eventually develop ND leading to doubts regarding the diagnostic utility of pseudodementia26. Personality changes are typical in early AD, particularly loss of extraversion and social assertiveness27, which may be mistaken for MDD-related social withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Although late-life depression may cause some cognitive impairment (i.e. “pseudodementia”), up to 70% of patients with pseudodementia will eventually develop ND leading to doubts regarding the diagnostic utility of pseudodementia26. Personality changes are typical in early AD, particularly loss of extraversion and social assertiveness27, which may be mistaken for MDD-related social withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, minor depression was found to constitute a clinically relevant syndrome of depression in Alzheimer’s disease (3). Depression can also be one of the earliest symptoms of AD (4–8). In addition, in a number of studies, it was found that a history of depression is a risk factor for the future development of dementia (9–14), and that the severity of psychopathological and neurological impairments in AD increases with the increasing severity of depression (3).…”
mentioning
confidence: 99%
“…On the other hand, it is well-known that reversible depression-related cognitive decline (also known as depressive pseudo-dementia) is often considered as true dementia and these patients do not receive adequate treatment for their mood disorder [22]. However, the depressive pseudo-dementia in old age seems to be a long-term predictor of true dementia [5,23].…”
Section: Discussionmentioning
confidence: 99%